UTILIZING OF STUDENTS TEAM WORK CORNER TECHNIQUE IN IMPROVING STUDENTS READING COMPREHENSION - Acep Bahrum Kamil (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2020)
The purpose of making this research was to know Utilizing of Students Team Work Corner (STWC) technique in Improving Students Reading Comprehension. Related to the problems that have found out taken from the observation time, such: They have lack of understand or poor in their vocabulary and feel bored while reading text, and students still confused how to get the information from content to definite main idea and so on reading text. The place for research was taken from Unsika at the first semester students in 2018. There are 60 students both of Experimental and control class students. The researcher tried out the method to cope the problems with STWC technique that is the simplest method of cooperative learning method. The main idea of STWC is to motivate the students in order to they can support and help each other. As regard the data interpretation and discussion in the previous chapter, the overall results of this research can be conducted by the researcher actually, that STWC technique could improve students reading comprehension going to high level.